Where No Gods Came - O'Connor, Sheila (Book collections on Project MUSE., 2003)
Where No Gods Came, the 2003 winner of the Michigan Literary Fiction Award for original novel, is a candid portrait of the unlikely faces of good and evil, and how an innocent must learn to recognize them to endure.